PENGARUH PERENCANAAN KARIR INDIVIDU DAN MANAJEMEN KARIR TERHADAP KEPUASAN KERJA. STUDI PADA KARYAWAN MANDIRI UNIVERSITY JAKARTA - Kristina Wine Prathita; Yohanes Arianto Budi Nugroho (Prosiding Working Papers Series In Management, 2018)
This study aims to examine the effect of individual career planning and career management on employee job satisfaction in Mandiri University Jakarta. Data were collected by distributing questionnaires to 50 employees of Kanwil Mandiri University Jakarta within one week given directly to employees. Sampling method used is convenience sampling. The data obtained is tabulated and processed, and then analyzed using the IBM SPSS Version 22 for windows statistics program. The results show that both partial and simultaneously individual career planning and management career variables have a significant effect on job satisfaction of employee in Mandiri University Jakarta. Keywords: individual career planning, management career and job satisfaction